2018
DOI: 10.1155/2018/4862480
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Structural Remodeling Gene Variants in Patients with Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is a common arrhythmia for which the genetic studies mainly focused on the genes involved in electrical remodeling, rather than left atrial muscle remodeling. To identify rare variants involved in atrial myopathy using mutational screening, a high-throughput next-generation sequencing (NGS) workflow was developed based on a custom AmpliSeq™ panel of 55 genes potentially involved in atrial myopathy. This workflow was applied to a cohort of 94 patients with AF, 76 with atrial dilatation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The myocardial hypertrophy commonly observed in high performance athletes may degenerate in fibrosis remodeling [64]. Furthermore, the severity extent in which fibrosis affects the cardiac function can be submitted to the interaction with multiple factors, such as, genetic conditions [65], gender [66] and ageing [67]. Moreover, in an AF scenario, the presence of fibrosis is expected to increase the proarrhythmic risk [15,18,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…The myocardial hypertrophy commonly observed in high performance athletes may degenerate in fibrosis remodeling [64]. Furthermore, the severity extent in which fibrosis affects the cardiac function can be submitted to the interaction with multiple factors, such as, genetic conditions [65], gender [66] and ageing [67]. Moreover, in an AF scenario, the presence of fibrosis is expected to increase the proarrhythmic risk [15,18,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…12,13 AKAP9 encodes for a scaffolding protein (A-kinase anchor protein 9) and is related to LQTS, BS, cardiomyopathy, atrial fibrillation, severe ventricular arrhythmia, and SUD. [14][15][16] Case 2 (family 2, II:1) with SUD had 3 missense VUS in the KCND3, AKAP9, and KCNE1 genes. The KCND3 gene encodes a member of the potassium channel, Potassium Voltage-Gated Channel Subfamily D Member 3.…”
Section: Discussionmentioning
confidence: 99%
“…RANGRF mutations were related to BS and histiocytoid cardiomyopathy in the literature 12,13 . AKAP9 encodes for a scaffolding protein (A-kinase anchor protein 9) and is related to LQTS, BS, cardiomyopathy, atrial fibrillation, severe ventricular arrhythmia, and SUD 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 94 patients with AF, a study screening for rare variants involved in atrial myopathy revealed a higher rate of variant carriers in patients presenting with atrial dilation. 66 Recent investigations strongly support the relevance of broader genetic background to atrial remodeling. 78,79 Atrial Features: Some Special Considerations…”
Section: Primary Atrial Structural Remodelingmentioning
confidence: 92%